Morbidity and Risk of Subsequent Diagnosis of HIV: A Population Based Case Control Study Identifying Indicator Diseases for HIV Infection - Søgaard, Ole S.; Lohse, Nicolai; Østergaard, Lars; Kronborg, Gitte; Røge, Birgit; Gerstoft, Jan; Sørensen, Henrik T.; Obel, Niels (PloS one, 2012)
Early identification of persons with undiagnosed HIV infection is an important health care issue. We examined associations between diseases diagnosed in hospitals and risk of subsequent HIV diagnosis. In this population-based case control study, cases were persons with incident HIV infection diagnosed in Denmark between 1 January 1995 and 1 June 2008. Risk-set sampling was used to identify 19 age- and gender-matched population controls for each HIV case, using the HIV diagnosis date as the index date for both cases and controls. Prior hospital diagnoses obtained from Danish medical databases were first categorized into 22 major disease categories (excluding AIDS-defining diseases except tuberculosis) and then subdivided into 161 subcategories, allowing us to examine specific diseases as potential HIV indicators by conditional logistic regression. The study included 2,036 HIV cases and 35,718 controls. Persons with the following disease categories had a high risk of HIV diagnosis during the subsequent 5-year period: sexually transmitted infections and viral hepatitis (adjusted odds ratio [aOR] = 12.3, 95% CI: 9.60-15.7), hematological diseases (aOR = 4.28, 3.13-5.85), lower respiratory tract infections (aOR = 3.98, 3.14-5.04)), CNS infections (aOR = 3.44, 1.74-6.80), skin infections (aOR = 3.05, 2.47-3.75), other infections (aOR = 4.64, 3.89-5.54), and substance abuse (aOR = 2.60, 2.06-3.29). Several specific diseases were associated with aORs >20 including syphilis, hepatitis A, non "A" viral hepatitis, herpes zoster, candida infection, endocarditis, thrombocytopenia, and opioid abuse. Targeted testing for HIV in patients diagnosed with diseases associated with HIV may lead to earlier treatment and thereby reduced morbidity, mortality and HIV transmission.